OPTIMIZATION OF SINKING FEED FORMULATION AND ADMINISTRATION STRATEGIES FOR ENHANCED CATFISH (Clarias sp.) PRODUCTIVITY IN PADANG BAKJOK VILLAGE, TANGAN-TANGAN DISTRICT, SOUTHWEST ACEH, ACEH, INDONESIA: OPTIMALISASI FORMULASI DAN STRATEGI PEMBERIAN PAKAN TENGGELAM UNTUK MENINGKATKAN PRODUKTIVITAS IKAN LELE(Clarias sp.) DI DESA PADANG BAKJOK KECAMATAN TANGAN-TANGAN ACEH BARAT DAYA, ACEH, INDONESIA - Nurhatijah; Indah Permatasari; Kurnia; Humeira; Masyitah; Husna (PT. ROCE WISDOM ACEH, 2025)
The purpose of this activity is to increase the awareness and capacity of the community in Padang Bak Jok Village, Tangan-Tangan District, Southwest Aceh Regency in making feed for catfish farming through education and training on the process of making and feeding sinking feed. The implementation method includes material presentation and field practice. The results showed an increase in the community's awareness and ability to calculate the amount of feed and feed-making/feeding techniques. This activity also encouraged the community to start a fish farming business with facilitation support from the Village Government and BUMG (Village-Owned Enterprises).